Regularity of Toll-Like Receptors in Bovine Mammary Epithelial Cells Induced by Mycoplasma bovis - Yang, Jinghan; Liu, Yuhui; Lin, Changjie; Yan, Rui; Li, Zhengzhi; Chen, Qiuhui; Zhang, Haiyan; Xu, Haojun; Chen, Xi; Chen, Yingyu; Guo, Aizhen; Hu, Changmin (Frontiers in Veterinary Science, 2022)
Abstract Mastitis is one of the most common and significant infectious diseases in dairy cattle, and is responsible for significant financial losses for the dairy industry globally. An important pathogen of bovine mastitis, Mycoplasma bovis (M. bovis) has a high infection rate, requires a long course of treatment and is difficult to cure. Bovine mammary epithelial cells (BMECs) are the first line of defense of the mammary gland, and their natural immune system plays a critical role in resisting M. bovis infection. This study aimed to explore and demonstrate the regularity of Toll-like receptors (TLRs) activation during M. bovis infection and their function during M. bovis mastitis. An in vitro model of M. bovis-induced mastitis showed that the expression of IL-6, IL-8, and TNF-α increased significantly following infection. M. bovis infection also upregulated the expression of TLR1/2/6 on the cell membrane and TLR3/9 in the cytoplasm. There is a crosstalk effect between TLR1–TLR2 and TLR2–TLR6. Furthermore, M. bovis infection was found to activate the TLR1/2/6/9/MyD88/NF-κB and TLR3/TRIF/IRF signal transduction pathways, which in turn activate inflammatory factors. These findings lay the theoretical foundation for understanding the pathogenesis of M. bovis, permitting the development of effective measures for preventing and controlling M. bovis mastitis.